Synthesis of Ketamine Derivatives by Mannich Reactions: Pharmaceutical Science-Microbiology - Muzzammil Masaud, Syed; Abbas Miana, Ghulam; Nazir, Taha; Rasheed Nazir, Saeed Ur; Riaz, Humayun; Sultana, Misbah; Sultana Munir, Safia; Akhtar Shah, Pervaiz; Nadeem, Humaira; Rabi, Ishtiaq (International Journal of Life Science and Pharma Research, 2022)
Arylcyclohexylamine Ketamine (HCL) has played an important role in Veterinary and Human Medicine as safe and reliable anesthetic agent but asit produces dysphoria several new derivatives of Ketamine have been synthesized till date. In this Research we have Utilized Mannich reaction to Synthesize The ammonia, primary amine and secondary amine are treated with hydrochloric acid and then added to the formaldehyde. Three novel derivatives were synthesized namely2-(2-chlorophenyl)- 6-[(diethyl amino) methyl]-2-(methylamino) cyclohexanone by RXN:102 Mannich Reaction of Ketamine with Di-ethylamine , rxn 113 2-(2chlorophenyl-6-dinitrophenyl hydrazine-methyl2(methylamino) cyclohexanone by Reaction of Ketamine with Di-nitro Phenyl Hydrazine & Rxn: 601. Mannich Reaction of Ketamine with Piperazine to form (2-chlorophenyl)-2-(methylamino)-6-(piperazine -1-yl) methyl cyclohexanone. Other reactions were also undergone to prepare oxazolidine derivatives of ketamine namely Synthesis of ketamine dioxolane derivative:Ketal and Hemiaminal Formation , Rxn: 103 Reaction of Ketamine with Glycerin [6-(2-chlorophenyl)-6-(methylamino)-1, 4-dioxaspiro [4.5] dec-2-yl] methanol and Rxn: 801 Reaction of Ketamine with Ephedrine N ,3,4-trimethyl-2,6 diphenyl-1oxa-4azaspiro [4.5] decan-6-amine derivative was formed. Thin layer chromatography of the synthesized derivatives was performed by using a solvent system of ethyl acetate and chloroform (50:50) and the RF values were calculated. The solubility test proves that compounds obtained from ketamine are polar in nature. All derivatives show similarity in solubility of ketamine. Although the melting points were not exactly comparable to that of ketamine, the range was not more than 5-10°C. This relatively narrow range of melting points proved that these were pure compounds. NMR spectroscopy was performed on all newly synthesized derivatives of ketamine. The notable ones obtained from reactions i.e. Rxn 102, 113, 103, 601and 801. The results of spectroscopy demonstrate that the compounds obtained were completely new species however they were structurally related to ketamine. These derivatives synthesized and confirmed by NMR technology. The derivatives can potentially be formulated for therapeutical purpose. Despite some limitations which are being considered in current drug design, the derivatives have the potential to develop into chemically modified entities that can play a major role in clinical therapeutics. Additional research studies will potentially help to determine the advanced method for high and sophisticated yield of these derivatives. Moreover, synthesis of ketamine metabolites namely N-demethyl compound and N-demethyl-5,6-dehydro analogues is established. However, further studies and modifications of these compounds will open new ventures of drug design and development of clinical implications in health care system.